Anthracene appended pyridinium amide–urea conjugate in selective fluorometric sensing of L-N-acetylvaline salt - Ghosh, Kumaresh; Sarkar, Tanmay; Chattopadhyay, Asoke P. (Beilstein Journal of Organic Chemistry, 2010)
A new anthracene labeled pyridinium amide–urea conjugate 1 has been designed and synthesized. The receptor shows a different fluorometric response with L-N-acetylvaline and L-N-acetylalanine salts in CH3CN in contrast to the other salts of L-N-acetyl α-amino acids and (S)-α-hydroxy acids studied. Upon complexation of the tetrabutylammonium salt of L-N-acetylvaline, the emission of 1 increases accompanied by the formation of a new band at higher wavelength and this characteristic change distinguishes it from other anionic substrates studied. The binding interaction has been studied by 1H NMR, fluorescence and UV titration experiments.
Keywords: N-acetyl-L-valine salt; DFT calculation; emission decay; fluorometric detection; pyridinium amide–urea conjugate